2021
DOI: 10.1186/s13023-021-02116-5
|View full text |Cite
|
Sign up to set email alerts
|

NeoSeq: a new method of genomic sequencing for newborn screening

Abstract: Objective To explore the clinical application of NeoSeq in newborn screening. Methods Based on the results obtained from traditional newborn screening (NBS) with tandem mass spectrometry (TMS), three cohorts were recruited into the present study: 36 true positive cases (TPC), 60 false-positive cases (FPC), and 100 negative cases. The dried blood spots of the infants were analyzed with NeoSeq, which is based on multiplex PCR amplicon sequencing. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The questionnaire was designed by the team at the Newborn Screening Center of Changzhou Maternal and Child Health Care Hospital, based on literature and previous clinical practice (8). The questionnaire consisted of four sections with 27 questions (Supplementary File 1).…”
Section: Questionnairesmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire was designed by the team at the Newborn Screening Center of Changzhou Maternal and Child Health Care Hospital, based on literature and previous clinical practice (8). The questionnaire consisted of four sections with 27 questions (Supplementary File 1).…”
Section: Questionnairesmentioning
confidence: 99%
“…In China, nGS is rapidly gaining traction. Beijing (6), Shanghai (7), and Jiangsu (8) have successively conducted relevant studies, such as NESTS and NeoSeq. These studies have confirmed that nGS could further expand the genetic diseases that could not be found by traditional screening methods, provided more genetic information, and showed great technical advantages and broad prospects for application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, newborn genomic sequencing (nGS) brings new opportunities to further expand newborn screening (NBS), which is an important public health project. 1 From 2013, BabySeq, 2 NBSeq, 3 NC NEXUS, 4 STATseq, 5 NESTS 6 and NeoSeq 7 successively confirmed that nGS could further expand the genetic diseases that could not be found by traditional screening methods and was considered as another innovation in the field of NBS. However, there are still many problems to be discussed and solved before large-scale clinical practice.…”
Section: Introductionmentioning
confidence: 93%
“…Commercially available targeted–sequencing tests can interrogate a finite number of genes associated with specific genetic disorders. These panels are less expensive than genomic sequencing, return results faster, and rarely identify secondary findings . A comparative analysis between genomic sequencing and a targeted neonatal gene-sequencing test has not been previously performed …”
Section: Introductionmentioning
confidence: 99%